Evaluación del potencial de germinación y vigor de semillas de cultivares de frejol. - Leal Bermello, Catherine Elizabeth (2016)
This research "Evaluation of potential seed germination and vigor of bean cultivars" was conducted at the Experimental Farm "La Maria" owned by the State Technical University of Quevedo, located at Km. 7½ via Quevedo- El Empalme. The overall objective was to determine the physiological potential of seeds of four varieties of beans; being its specific objectives establish the viability or potential germination of seeds of beans at the level of field and laboratory, compare the agronomic characteristics and performance of each of the varieties of beans. In the field phase the experimental design was used Blocks Randomized Complete (DBCA) and in the laboratory stage the Completely randomized design (DCA) with four treatments and four repetitions. The genetic material was composed of bean cultivars Panamito, Cuarentón, Tumbe y Pata de Paloma. The field experiment was conducted during the period July to November 2015 and the laboratory stage in the months of January and February 2016. Field-level planting was used a distance of 0.60 x 0.30 m with a net plot of 24 plants per replication. Agronomic tasks necessary for crop development as they were made: soil preparation, marking the lot, disinfection seeds, planting, thinning, fertilization, weed control, irrigation and harvesting The variables recorded in the field were: percentage of plant emergence in the field, number of days to flowering, plant height (cm), vigor, percentage of plant survival, number of pods per plant, number of seeds per plant, weight 100 seeds (g), dry grain yield (kg / ha); Laboratory: germination percentage, root length and aerial part, and cold test. The study data were subjected to analysis of variance and comparisons between treatment means were made by Tukey test at 95% probability. The results indicate the following: Tumbe cultivar presented at 10 and 15 days, the highest percentage of plant emergence with 95 and 96.50%, respectively, representing that this genotype has a good germination, also had the highest plant height of 78.93 cm, excellent vigor, the highest percentage of survival of plants with 97.92%, the highest number of seeds per pod with 10.63, the highest number of seeds per plant with 281.28 and higher yield of dry grain 3316.52 Kg / ha. Cuarentón cultivar was earlier flowering with 31.56 days lower average plant height of 36.08 cm with greater weight of 100 seeds with 48.8 g; Panamito cultivar had the highest average with 29.30 pods per plant